Decoding Therapeutic Applications of Quercetin: Recent Advancements in Nanotechnological Strategies - Grewal, Sonam; Tiwary, Neha; Malik, Gaurav; Garg, Madhukar; Deswal, Geeta; Chopra , Bhawna; Grewal, Ajmer Singh; Dhingra, Ashwani K.; Guarve, Kumar (Pharmaceutical Nanotechnology, 2025)
For centuries, people have used herbal medicine to treat a diversity of health complications and as a natural substance, they have a favourable effect on our health. Herbal ingredients can be utilized as lead molecules in the innovation and development of a new drug. Flavonoids are a class of chemical compounds with diverse phenolic structures, and they are found in a wide variety of foods, including fruits, vegetables, cereals, bark, roots, stems, flowers, tea, and wine. Quercetin is the most prevalent polyphenolic bioflavonoid or flavonoid. Quercetin is found in many food products and has demonstrated a wide range of pharmacological activities, including the treatment of allergies, ocular diseases, metabolic ailments, inflammatory illnesses, cardiovascular ailments and arthritis. Quercetin has attracted interest as an emerging pharmacophore with the potential to significantly advance research and the development of novel therapeutic medicines for a variety of diseases. Despite having a huge therapeutic potential, these flavonoids have unfavourable pharmacokinetic characteristics, low bioavailability, and poor solubility, limiting their application in therapeutics. The objective of the current study is to present a new update on the major therapeutic uses of quercetin and other types of nanocarriers that contain quercetin to treat various ailments.
Keywords: natural compounds